2005
DOI: 10.1088/0022-3727/39/1/020
|View full text |Cite
|
Sign up to set email alerts
|

Energy properties of an EMI-Im ionic liquid ion source

Abstract: The identity and the energy distributions of positive and negative ions electrostatically extracted from the liquid phase in an ionic liquid ion source (ILIS) are analysed with a time-of-flight mass spectrometer and a multi-grid retarding potential analyzer. Accurate energy measurements using ionic liquids in an externally wetted configuration are reported for the first time. Droplet-free beams are produced using the ionic liquid 1-ethyl-3-methylimidazolium bis(triflouromethylsulfonyl)amide (EMI-Im) in which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
99
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 21 publications
8
99
1
Order By: Relevance
“…Energy measurements of ILIS beams have indicated that fragmentation events from solvation n to n − 1 are dominant [34]. Neglecting other transitions, the ion and neutral fractional kinetic energies are then simply related to the flight time as the functions…”
Section: Indirect Performance Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy measurements of ILIS beams have indicated that fragmentation events from solvation n to n − 1 are dominant [34]. Neglecting other transitions, the ion and neutral fractional kinetic energies are then simply related to the flight time as the functions…”
Section: Indirect Performance Calculationsmentioning
confidence: 99%
“…The accelerating voltage V a will generally differ from the applied emitter voltage V em by some deficit ΔV . Reported values of ΔV range from a few volts [34,36] to more than 100 V [4] depending on the source and operating conditions. Energy deficits may include intrinsic physical mechanisms, such as the ion solvation energy and Ohmic losses at the Taylor cone apex, or external influences such as series resistances upstream electrical path.…”
Section: Indirect Performance Calculationsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Since the physical and chemical properties of ILs can be varied by the choices of the cation and anion pair, 1 they can be used for many applications such as fuel cells, [3][4][5] batteries 6,7 and solar cells. 8,9 Furthermore, ILs are also used in ionic propulsion, 10,11 for hypergolic fuels 12 and various chemical extraction applications. 13 The vast number of possible anion-cation combinations 14 makes it valuable to rationally predict IL properties based on their constituents, 15 and considerable experimental and theoretical work has been performed to predict and measure ionic liquid properties.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the measured thrust being lower than that calculated is consistent with some population of emitted particles becoming neutral prior to the electrostatic gate, a phenomenon known to occur through fragmentation of solvated ions in flight. 35 The minimum thrust measured with the thrust-stand is below 50 nN. The use of a sensing plate, and the low noise levels and vibration immunity it affords, is thus validated by the agreement between the thrust measurements using two different techniques.…”
Section: Thrust Measurement From An Electrospray Devicementioning
confidence: 86%